VARIASI BAKTERI PADA PENDERITA INFEKSI SALURAN KEMIH (ISK) - Yashir, Muhammad; Apriani, Apriani (JURNAL MEDIA KESEHATAN, 2019)
Urinary Tract Infection (UTI) is the second most common infectious disease after respiratory tract infection and as many as 8.3 million cases are reported per year. In Indonesia the prevalence of UTI ranges from 5-15% and the number of UTI patients reaches 90-100 cases per 100,000 population per year. gold standard of ISK proof by performing microbiological examination that is urine culture and routine urinalysis examination of dyeing method. This study aims to find out the description of urine culture laboratory results on leukocyte esterase and Erythrocytes, and to see the presence of bacterial variation in isk sufferers at Atmajaya Hospital, North Jakarta. Research Methods Descriptive analysis of 33 samples or respondents of all ages without limitation in Microbiology Laboratory Atmajaya Hospital November - December 2017. The results of the number of female respondents (52%) more than men (48%). The incidence of UTI was increased in patients over 40 years of age, 41-60 years (10 cases), and> 60 years (10 cases). From this study, Escherichia coli (31%) is the most common microorganism that causes UTI.